An efficient heterogenized palladium catalyst for N-alkylation of amines and α-alkylation of ketones using alcohols1. Issue 53 (11th June 2015) - Dang, Tuan Thanh; Shan, Siah Pei; Ramalingam, Balamurugan; Seayad, Abdul Majeed
<x xml:space="preserve">Abstract</x> Silica supported palladium–NiXantphos complex is an efficient and high turnover heterogeneous catalyst for N-alkylation of amines and α-alkylation of ketones using alcohols under neat conditions at 120–140 °C following hydrogen borrowing strategy.